497 THE USE OF A NEW PRESENTATION FORMAT IMPROVES PATIENT CARE AND TEACHING IN THE INTENSIVE CARE UNIT. (1st January 2006) - Kamali, J.; Zamora, E.; Chang, B.
Abstract : Purpose: Intensive care unit (ICU) patients require a detailed, accurate assessment and plan for optimal care. We conducted a study to determine how a well-organized, daily progress note can help the housestaff understand the complex ICU issues, improve documentation, and optimize application of standard of care. Methods: Thirty-three interns, 9 medical students, and 7 intensivists in two affiliated institutions, a university hospital and a VA hospital, participated in this study. The housestaff were observed for 4 months. During the first 2 months, housestaff used their own or institution's progress notes and presentation format. After 2 months, the new standardized progress note was introduced and housestaff were asked to present and document using the new format. Housestaff and intensivists completed questionnaires assessing several areas during observation and intervention months. The survey included documentation of relevant data, application of ICU standards of care (such as daily discontinuation of sedation, GI and DVT prophylaxis), and presentation of problem list and plan. A total of 320 valid evaluation forms were submitted. Results: Subjective evaluation by the housestaff did not considerably change, ranking themselves high regardless of intervention. Intensivists, however, noticed in the intervention group significant improvement in identification and documentation of relevant data (50% vs 73%, p < .01), presentation of assessment and plan (57% vs 76%, p < .01), and appropriate application of certain ICU standards in patient care, such as GI prophylaxis (63% vs 87%, p < .01) and DVT prophylaxis (66% vs 86%, p < .01) with the standardized progress note. Documentation and presentation areas that did not significantly improve were daily discontinuation of daily sedation (62% vs 70%, p .15) and ventilator weaning (58% vs 62%, p .56). Conclusions: We believe this is the first study assessing the impact of a standardized presentation format on applying well-established ICU standards by residents. Based on intensivists' evaluations, this format improves patient care in several areas, as well as documentation, accurate assessment and plan, and therefore, likely, resident teaching.